A meta-analysis of the impacts of operating in-vehicle information systems on road safety. (October 2019) - Ziakopoulos, Apostolos; Theofilatos, Athanasios; Papadimitriou, Eleonora; Yannis, George
Abstract: This study aims to estimate the overall impact of distraction due to operating in-vehicle information systems (IVIS) and similar devices while driving on road crashes. While similar research has been undertaken investigating the issue, varying results have been reported so far. Therefore a two-step approach was adopted: initially a review of the literature was conducted to identify key high quality studies and the parameters that they examined. Afterwards, meta-analyses were applied in order to estimate the overall effects of operating IVIS while driving on the absolute proportion of crashes (i.e. the proportion of total crashes due to IVIS). After applying a random effects meta-analysis to the findings of existing studies, it was found that 1.66% of crashes occur due to operating devices in total. In addition, it is indicated that about 0.6% of safety-critical incidents for professional drivers are due to in-vehicle device operation. The odds of crashes influenced by IVIS operation were also estimated and were found to be very low. From the findings of the present review and the meta-analysis, it is suggested that device operation as a risk factor while driving is a less researched aspect of driver distraction than others, and more studies would improve result estimates and transferability, especially for professional drivers. This study summarizes concisely the current effect of driver interaction with in-vehicle information systems on crashes, which might become considerably pertinent in view of the increasing deployment of vehicles with increasing levels of automation. Highlights: This paper conducts a review on the effect of operating in-vehicle systems on crashes. Random effects meta-analysis techniques are conducted afterwards on selected studies. 1.66% of total crashes are caused by operating in-vehicle systems. The respective proportion is 0.60% when examining professional drivers only.